LINGVO-CULTURAL FOUNDATIONS OF COMPAROVESTICS IN WORKS TRANSLATED FROM ENGLISH INTO UZBEK - Mahmudova Zarifa Tolib qizi, Mahmudova Zarifa Tolib qizi; Yaxshiyeva Zebo Rashidovna (Modern American Journals, 2025)
The article is devoted to the study of the linguo-cultural foundations of comparative studies by the example of works translated from English into Uzbek language. The inextricable link between language and culture and the importance of cultural context in translation are emphasized. Comparative techniques help to identify linguistic and cultural gaps, improving the quality of translation and cross-cultural communication. Therefore, a linguo-cultural approach is important to enhance the depth of translation and to strengthen the inter-literature ties.